A Compliant Telescopic Limb with Anisotropic Stiffness - Fishman, Aaron; Garrad, Martin Stephen; Hinitt, Andrew; Zanini, Plinio; Barker, Tim; Rossiter, Jonathan (Frontiers in Robotics and AI, 2017)
Soft limbs with anisotropic stiffness are common in nature and enable animals to solve a variety of tasks, including locomotion and manipulation. This mixture of hardness and softness enables animals to efficiently control the unpredictable contact forces that occur while performing such tasks. A challenge for soft robotics is to create artificial limbs that mimic natural mixtures of hardness and softness for use as a building block for soft, adaptable robots. This article presents the design of a novel pneumatic limb module with adjustable length and anisotropic stiffness. The artificial limb is designed with a rigid telescopic endoskeleton inside a rubber bellow, which we show is able to resist buckling, while remaining externally soft. Finally, we present the design of a hexapod walker based on the limb units.